2015
DOI: 10.2108/zs140129
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Phylogenetic Relationships of the Asian-Pacific Endemial Subterranean Amphipod Genus Pseudocrangonyx Among Families and Genera of Crangonyctoidean Amphipods Inferred by Partial LSU rDNA Gene Sequences

Abstract: To analyze the phylogenetic relationships of the genus Pseudocrangonyx within the superfamily Crangonyctoidea, we sequenced a partial LSU rDNA gene from four species (six specimens). The monophyly of Pseudocrangonyx and its affinity to Crymostygius were strongly supported by four reconstruction methods: neighbor-joining, minimum evolution, maximum-likelihood, and Bayesian inference. Current geographical distributions of the taxa studied and their phylogenetic relationships established in our study suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Pseudocrangonyctidae and Crangonyctidae, inhabit groundwater habitats in caves, springs, and hyporhea (Holsinger 1994 ). Although the previous study showed the monophyly of Crangonyctidae + (Pseudocrangonyctidae + the Icelandic subterranean Crymostygius ) (Sidorov and Gontcharov 2015 ), the precise phylogenetic relationship of the 14 crangonyctoidean families remains unresolved.…”
mentioning
confidence: 98%
“…Pseudocrangonyctidae and Crangonyctidae, inhabit groundwater habitats in caves, springs, and hyporhea (Holsinger 1994 ). Although the previous study showed the monophyly of Crangonyctidae + (Pseudocrangonyctidae + the Icelandic subterranean Crymostygius ) (Sidorov and Gontcharov 2015 ), the precise phylogenetic relationship of the 14 crangonyctoidean families remains unresolved.…”
mentioning
confidence: 98%
“…Seven genera out of the 110 identified (or 6.4%) belong to the paleolimnic complex (the genus Pseudocrangonyx presumably attributed to this group). It is the underground amphipods from the families Crangonyctidae and Pseudocrangonyctidae which are the most ancient freshwater inhabitants [Sidorov, Gontcharov, 2015].…”
Section: Onisimus Birulaimentioning
confidence: 99%
“…However, their zoogeographical heterogeneity is of interest; the underground representatives belong to four biogeographic groups (see Table 4). Four groups could be identified, which differ markedly in their origin and evolution: 1) Holarctic group of the paleolimnic complex Crangonyx-Synurella; 2) a group of the Western Palearctic Niphargidae, related to the mesolimnic complex; 3) a group of the Far Eastern Pseudocrangonyctydae of unknown origin [Sidorov, Gontcharov, 2015], and 4) a group of the neolimnic Far Eastern Ganigamoera [Sidorov, 2010].…”
Section: Gammarus Lacustrismentioning
confidence: 99%
“…The two exclusively subterranean amphipod families Niphargidae Bousfield, 1977, distributed mainly in Europe, (Copilaş-Ciocianu et al, 2019. Pseudocrangonyctidae is phylogenetically related to the Crymostygidae Kristjánsson and Svavarsson, 2004 distributed in Iceland, suggesting that their common ancestor was present in the Arctic Basin (Sidorov and Gontcharov, 2015). The distribution of the family, including Pseudocrangonyx, is restricted from subarctic to temperate zones.…”
Section: Introductionmentioning
confidence: 99%